Relicts in the mist: Two new frog families, genera and species highlight the role of Pantepui as a biodiversity museum throughout the Cenozoic - Antoine Fouquet; Philippe J.R. Kok; Renato Sousa Recoder; Ivan Prates; Agustin Camacho; Sergio Marques-Souza; José Mario Ghellere; Roy W. McDiarmid; Miguel Trefaut Rodrigues (Molecular Phylogenetics and Evolution, 2024)

Reconquering the water: Evolution and systematics of South and Central American aquatic lizards (Gymnophthalmidae) - Sergio Marques‐Souza; Ivan Prates; Antoine Fouquet; Agustín Camacho; Philippe J. R. Kok; Pedro M. S. Nunes; Francisco Dal Vechio; Renato Sousa Recoder; Nathalia Mejia; Mauro Teixeira Junior; Cesar Barrio‐Amorós; José Cassimiro; et al. (Zoologica Scripta, 2018)
The Cercosaurini tribe stands out from other Gymnophthalmidae lizards for including several species with morphological adaptations to aquatic lifestyle (“Crocodile‐Like Morphology” – CLM ). Recent molecular phylogenies of Cercosaurini demonstrated the paraphyly of CLM species, implicitly suggesting that adaptations to the aquatic life evolved more than once. However, CLM species have remained poorly sampled, and a number of uncertainties persist, such as the monophyly of Neusticurus and the placement of Potamites apodemus within the tribe. Based on a more extensive molecular and morphological data set, we propose a phylogenetic hypothesis for Neusticurus and investigate, for the first time, the phylogenetic position of P . apodemus . We recovered a monophyletic Neusticurus clade; however, Neusticurus rudis as currently understood was recovered as paraphyletic, with two lineages that also show consistent morphological diagnosis; as a result, we resurrect and provide a taxonomic redescription of Neusticurus surinamensis Müller, . Moreover, because P. apodemus was recovered as sister to all other Echinosaura , we propose a new combination for this species ( Echinosaura apodema ). We also review the distribution of Neusticurus species, offering a comprehensive view of their biogeography. Lastly, our ancestral character reconstruction and dating analyses indicate that the CLM phenotype evolved four times independently during Cercosaurini′s evolutionary history. We hypothesize that the CLM phenotype and subsequent adaptation to aquatic life may be linked to the development of the Pebas Lake in western Amazonia during the Miocene.